2016
DOI: 10.1021/acs.jced.5b00981
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Spectral Studies for SO2 in a Binary System of Triethylene Glycol + Dimethyl Sulfoxide at T = (298.15, 303.15, and 308.15) K and p = 123.15 kPa

Abstract: In this work, isothermal gas−liquid equilibrium (GLE) data were measured for the mixture SO 2 + N 2 in the system of triethylene glycol (TEG) + dimethyl sulfoxide (DMSO) at T = (298.15, 303.15, and 308.15) K and p = 123.15 kPa. Henry's law constants (HLCs) were obtained by fitting the linear slope of the GLE data. The results indicated that the solubility of dilute SO 2 in the system of TEG + DMSO increased with the increasing DMSO concentrations, and HLCs decreased with the increasing temperatures. The regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…As shown Figure a, two absorption bands were observed at nearly 278 and 212 nm, which was due to the n →π* electronic transition of SO 2 at longer wavelength and n →σ * for O atom in PGME or π → π* for SO 2 at shorter wavelength . The absorption intensity of the band at nearly 278 nm increases with the increasing SO 2 concentration, which may result from the probability of electronic transition of n→ π* for SO 2 increase when the SO 2 concentration increase.…”
Section: Results and Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…As shown Figure a, two absorption bands were observed at nearly 278 and 212 nm, which was due to the n →π* electronic transition of SO 2 at longer wavelength and n →σ * for O atom in PGME or π → π* for SO 2 at shorter wavelength . The absorption intensity of the band at nearly 278 nm increases with the increasing SO 2 concentration, which may result from the probability of electronic transition of n→ π* for SO 2 increase when the SO 2 concentration increase.…”
Section: Results and Discussionmentioning
confidence: 81%
“…As shown in Figure , the solubility of SO 2 in the binary system of PGME (1) + DMSO (2) increased when DMSO concentrations increased, and the solubility of SO 2 presented a minimum value (0.0074 mol·kg –1 ) in pure PGME; meanwhile, the pure DMSO ( w 1 = 0%) showed the maximum value of 0.0781 mol·kg –1 to dissolve SO 2 . , In addition, the absorption capacity of SO 2 in the system of PGME + DMSO were stronger than PEG300 + DMSO and TEG + DMSO systems at the same alcohol ratio.…”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…FTIR was employed to analyze the composition and surface functional group changes of the U-β-Ni­(OH) 2 /NF and U–Fe-β-Ni­(OH) 2 /NF-2 samples (Figure b). The intense bands from 3200–3500 cm –1 for NiC 2 O 4 /NF and FeNi–C 2 O 4 /NF samples belong to the stretching vibration bands of the hydroxyl group in H 2 O. , Two relatively weak bands at 2916 and 2846 cm –1 and the band at nearly 1614 cm –1 correspond to the CH stretching model of the carbon chain as well as the asymmetric stretching vibration model of the CO group, respectively. , Also, the bands at 1358, 1313, and 823 cm –1 signify the characteristic peak of the CO group, and the 753 cm –1 corresponds to the stretching vibration of the NiO group. , Furthermore, we found that the peaks of the NiO group in FeNi–C 2 O 4 /NF are expressed at a lower wavenumber region compared to NiC 2 O 4 /NF, suggesting that the Fe introduced into NiC 2 O 4 weakens the bond strength of the NiO group, causing an increase in bond length. After the anion-exchange reaction, we observed a narrow and sharp band for a stretching vibration peak of a non-hydrogen-bonded, geminal, free hydroxyl group in U-β-Ni­(OH) 2 (3640 cm –1 ). , The peak intensity decreased with a feed ratio of Fe, most likely caused by the introduction of Fe into Ni­(OH) 2 , which decreased the intensity of the original NiOH group.…”
Section: Resultsmentioning
confidence: 95%
“…8 Therefore, it is necessary to select new efficient, economical, and renewable types of organic solvents. Qiao 9 reported the solubility of SO 2 in trimethylene glycol (TEG) and dimethyl sulfoxide (DMSO), which absorbed about 0.56 g of SO 2 per 1.00 g of solvent. Thus, Shi et al 10 used tetraethylene glycol (TeEG) + DMSO to absorb SO 2 at an absorption of 0.57 g/g.…”
Section: Introductionmentioning
confidence: 99%